2019
DOI: 10.1115/1.4043343
|View full text |Cite
|
Sign up to set email alerts
|

Nonaxisymmetric Stator Design for Boundary Layer Ingesting Fans

Abstract: In a boundary layer ingesting (BLI) fan system, the inlet flow field is highly nonuniform. In this environment, an axisymmetric stator design suffers from a nonuniform distribution of hub separations, increased wake thicknesses, and casing losses. These additional loss sources can be reduced using a nonaxisymmetric design that is tuned to the radial and circumferential flow variations at exit from the rotor. In this paper, a nonaxisymmetric design approach is described for the stator of a low-speed BLI fan. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On the other hand, the influence of inlet distortion has always been an extensive subject of research due to its detrimental effects on the stall margin [22,23]. With the current trend in the Boundary Layer Ingestion technology to improve the propulsive efficiency, the aerodynamic and aeroelastic response of the fan to inlet distortion has been received an increasing attention [24][25][26][27]. If blade shapes are assumed to be identical, the flow field subject to a circumferential inlet distortion can be computed using a single-passage solution with the current stateof-the-art based on the Fourier method [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the influence of inlet distortion has always been an extensive subject of research due to its detrimental effects on the stall margin [22,23]. With the current trend in the Boundary Layer Ingestion technology to improve the propulsive efficiency, the aerodynamic and aeroelastic response of the fan to inlet distortion has been received an increasing attention [24][25][26][27]. If blade shapes are assumed to be identical, the flow field subject to a circumferential inlet distortion can be computed using a single-passage solution with the current stateof-the-art based on the Fourier method [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…However, while the BLI fan layout brings aerodynamic advantages, it also introduces a specific type of spatially nonuniform inflow condition known as BLI inlet distortion. This distortion significantly reduces the fan’s aerodynamic performances (Gunn and Hall, 2014; Gunn and Hall, 2019), consequently undermining the potential aerodynamic benefits of the aircraft. In addition, the distortion intensity will vary with flight conditions due to the variable amount of boundary layer ingested by the fan (Hall et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, as the BLI fan operates from near choke to near stall point, the loss variations of the rotor blade passages at different annulus locations present complex and diverse characteristics. Further, the diverse loss variation trends could be affected by multiple predominant flow features in BLI inflow, including a reduction in axial velocity due to ingesting low-momentum boundary layer fluid, swirl induced by pressure gradients in circumferential direction and streamtube contraction caused by flow redistribution (Gunn and Hall, 2014; Gunn and Hall, 2019). These flow features are highly coupled, making it extremely hard to identify the influence of each flow feature on the loss.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the adverse impact of BLI distorted inflow on the fan aerodynamic performance, an effective fan blade design strategy that aims to reduce the additional loss in the BLI fan is necessary. The research work conducted on blade design has demonstrated that reducing the flow separation loss in the BLI fan stator is probably a good way to improve the fan efficiency effectively [19]. In this situation, it is essential to find a good way to suppress the flow separations in the stator to reduce the additional loss and further improve the aerodynamic performance of the BLI fan.…”
Section: Introductionmentioning
confidence: 99%